MENTAL BARRIERS TO REDUCE VULNERABILITY TO INJURY DURING A FALL: AN ELEMENTARY ISSUE OF PERSONAL SAFETY IN A GLOBAL CIVILIZATION - Bartłomiej Gąsienica-Walczak; Artur Kalina; Artur Litwiniuk; Joanna Baj-Korpak (Health Problems of Civilization)
The effects of unintentional human falls are seen as a serious public health problem. The cognitive aim of the study was to argue, based on evidence, that radical progress in preventing the consequences of unintentional falls is possible as long as mental barriers are broken down among actors with the potential competence to make changes from the micro to macro scale. Aa a method, a narrative review was used of publications documenting the achievements of the experts of the “Polish School of Safe Falling” regarding the mental aspects of the widespread implementation of methods to reduce the phenomenon of vulnerability to injuries during falls throughout the entire ontogeny. Participants in the main pedagogical experiments declared that: teaching safe fall techniques made sense for both healthy and high-risk individuals (95% of physiotherapy students’ responses); all amputees and 83% of patients with visual impairment were convinced that teaching safe fall techniques in high-risk fall groups made sense; one response from a patient with visual impairment (16%) was “I don’t know”, and none of the respondents denied the advisability of teaching safe fall techniques. The child’s natural ability to protect their hands and head during an unintentional fall begins to be lost by the age of three. Therefore, learning how to fall safely is the surest of ways to reduce the number of people who would spend the rest of their lives in disability as a result of injuries sustained in a fall.